A depressing view of hormonal contraception?. Issue 10 (October 2017) - Burket, Jeffrey; O'Mara, Heather; Thompson, Richard; Arnold, Michael; Neff, Laurel
Abstract : N/A: Skovlund CW, Mørch LS, Kessing LV, Lidegaard ø. Association of hormonal contraception with depression. JAMA Psychiatry . 2016; 73(11):1154–1162.